Breath Alkane as an index of severity for oral submucous fibrosis: A new perspective?. (January 2017) - Arakeri, Gururaj; Boraks, George; Aljabab, Abdulsalam S.; Patil, Shekar Gowda; Merkx, M.A.W.; Brennan, Peter A.
Abstract: Oral submucous fibrosis (OSMF) is a devastating disease commonly seen in the Asian subcontinent that results in significant functional morbidity for patients and has a high potential for malignant transformation. Over the last three decades, different diagnostic methods have been described to quantify and grade OSMF severity. Some methods have been used with perceived favorable outcomes although recurrence and malignant transformation remains a problem in many cases, and OSMF presents a major therapeutic challenge. We present a simple, noninvasive and less time-consuming diagnostic method which measures the severity of OSMF, helping to predict its malignant transformation and monitoring the effect of medical therapy on this disease.